Study on reducing power of Morinda citrifolia L. Fruit Extract (McFE) as a reduced agent in the green synthesis of gold nanoparticles - Du, Dang Xuan; Nguyễn , Thị Ngọc Thúy; Trần, Thị Minh Mẫn; Trịnh, Đức Tiến (Hue University Journal of Science: Natural Science, 2024)
The reducing power of Morinda citrifolia L. Fruit Extract (McFE) for the green synthesis of gold nanoparticles was evaluated by ferricyanide method, infrared spectroscopy (FT-IR) and ABTS•+ free radical scavenging activity. The results showed that the extract sample at the concentration of 75 mg/mL (McFE75) stored for 2 days gave the highest reducing power. FTIR spectroscopy indicated the involvement of carboxyl, amine and hydroxyl groups in the the composition of McFE75. Gold nanoparticles (AuNPs) were green synthesized using McFE75 as a reducing agent with a volume ratio of McFE75/Au3+ 1 mM of 1:10. The UV-vis spectroscopy, TEM and SEM methods were used to monitor the formation and morphology of AuNPs. The Zeta potential method was used to evaluate the stability of the gold colloidal system. The results showed that the time of 110 minutes was suitable to fabricate the gold nano colloidal system at room temperature. The size of obtained AuNPs was of about 17 nm, Zeta potential = -14.2 mV. The obtained nano gold colloidal system was quite stable. After 2.5 months of storage, the size and Zeta potential of AuNPs were 26 nm and -6.5 mV, respectively.